2021
DOI: 10.1007/s13659-021-00317-w
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Potential Lead Compounds for Drug Discovery Against SARS-CoV-2

Abstract: For the past 2 years, the coronavirus responsible for the COVID-19 infection has become a world pandemic, ruining the lives and economies of several nations in the world. This has scaled up research on the virus and the resulting infection with the goal of developing new vaccines and therapies. Natural products are known to be a rich source of lead compounds for drug discovery, including against infectious diseases caused by microbes (viruses, bacteria and fungi). In this review article, we conducted a literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 155 publications
(219 reference statements)
0
18
0
Order By: Relevance
“…Since the outbreak of the COVID-19 pandemic, numerous single herbs and herbal formulations as well as single compounds isolated from the herbal extracts have been reported to exhibit significant anti-SARS-CoV-2 effects through the inhibition of SARS-CoV-2 life cycle by targeting viral proteins such as 3CLpro, PLpro, RNA-dependent RNA polymerase (RdRp), and S protein, and cellular proteins such as ACE2, cathepsin L, and TMPRSS2 (Adeleye et al, 2022;Benarba & Pandiella, 2020;Lee, Park & Cho, 2022). Saponins including triterpenoid saponins derived from various medicinal plants have also been investigated for their therapeutic potential against SARS-CoV-2 (Ebob, Babiaka & Ntie-Kang, 2021). But, most are based on in silico studies (Diniz, Perez-Castillo, Elshabrawy, Filho & de Sousa, 2021;Falade, Adelusi, Adedotun, Abdul-Hammed, Lawal & Agboluaje, 2021;Sinha et al, 2021;Yang et al, 2020) and it is only recently that their inhibitory activities have been demonstrated using pseudotyped or authentic SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Since the outbreak of the COVID-19 pandemic, numerous single herbs and herbal formulations as well as single compounds isolated from the herbal extracts have been reported to exhibit significant anti-SARS-CoV-2 effects through the inhibition of SARS-CoV-2 life cycle by targeting viral proteins such as 3CLpro, PLpro, RNA-dependent RNA polymerase (RdRp), and S protein, and cellular proteins such as ACE2, cathepsin L, and TMPRSS2 (Adeleye et al, 2022;Benarba & Pandiella, 2020;Lee, Park & Cho, 2022). Saponins including triterpenoid saponins derived from various medicinal plants have also been investigated for their therapeutic potential against SARS-CoV-2 (Ebob, Babiaka & Ntie-Kang, 2021). But, most are based on in silico studies (Diniz, Perez-Castillo, Elshabrawy, Filho & de Sousa, 2021;Falade, Adelusi, Adedotun, Abdul-Hammed, Lawal & Agboluaje, 2021;Sinha et al, 2021;Yang et al, 2020) and it is only recently that their inhibitory activities have been demonstrated using pseudotyped or authentic SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Research related to the management of the disease has culminated in a record number of publications, including a significant amount of work investigating natural compounds in the context of COVID-19. To date, relevant secondary (review) studies have focused either on natural products with known antiviral properties associated with other viral infections (in the sense that some of these properties may render them effective against COVID-19) ( Dejani et al, 2021 ; Ebob et al, 2021 ) or were not focused on single classes of compounds ( da Silva, 2021 ; Ghidoli et al, 2021 ; Khazeei Tabari et al, 2021 ; Kowalczyk et al, 2021 ; Montenegro-Landivar et al, 2021 ) or elaborated on synthetic antiviral regimens ( Shah et al, 2021 ). To the authors best knowledge, a review summarizing the evidence about natural products of different classes on COVID-19 has not been published so far.…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 99%
“…Additionally, NPs are currently employed in medicinal chemistry to develop new chemotherapies, for example, neurodegenerative [ 16 ], cancer [ 17 ], immune-related [ 18 ], liver [ 19 ], and kidney [ 20 ] diseases, to mention a few examples. Moreover, during the current pandemic outbreak, NPs have been a rich source for discovering potential lead compounds against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%